Cafe choices of youth: perspective of university students / Jewel Joy Justinus … [et al.] - Justinus, Jewel Joy; Abdullah, Mohd Zahirduddin; Haguan, Sofi Sohana; Aziz, Adrianna (Universiti Teknologi MARA, Sabah, 2024)
Attracting customers to a café requires more than just offering delectable food options. Thus, the purpose of this study is to gain a comprehensive understanding of why youth from Universiti Teknologi MARA (UiTM) Sabah branch visit cafes in Kota Kinabalu, Sabah. The study aims to identify the five atmospheric-related factors such as facility aesthetics, lighting, ambience, spatial arrangement, and ambient intelligence that drive these visits and how these factors impact the choices and experiences of the youth. By focusing on this demographic and location, the researchers can provide valuable insights into the motivations behind café visits and potentially contribute to the cafe industry, urban planning, and marketing strategies tailored to this target audience. A quantitative method was used to distribute the online questionnaires. 230 students participated in the study. The study sheds insights into the significance of various atmosphere factors and provides valuable guidance for café owners and marketers aiming to cater to the preferences of young customers. Finally, implications for future studies are suggested.